Aplikasi Business Intelligence Pada Sistem Penjualan CV. Muda Jeans - Erik Rahman (Explore, 2024)
This research explains the application of business intelligence in Point of Sales sales applications in CV. Young Jeans. Muda Jeans is a private company that buys, sells, and manufactures women's jeans. The authors used a descriptive method in this study and conducted observations and interviews with store owners and employees. The sales system currently used by CV. Muda Jeans uses a traditional sales system where the entire sales transaction process is carried out directly through store visits and every transaction is recorded in the general ledger, this results in data recording errors, data duplication and data presentation which can cause problems in data utilization. Data utilization is used in decision making in creating and developing new products. This problem can be overcome with Point of Sales applications that apply business intelligence, allowing applications to analyze current and historical data displayed through data visualization. Data visualization in the form of sales graphs per product to make it easier for owners to see, understand and analyze product movements through sales transactions that occur, which products will later be increased production, which products are decided to be reduced or not produced at all.